2 | ( | X | − | 2 | ) | − | ( | 3 | X | − | 1 | ) | = | 4 | ( | 1 | − | X | ) |
方程左边 = | 2 | X | − | 2 | × | 2 | − | ( | 3 | X | − | 1 | ) |
= | 2 | X | − | 4 | − | ( | 3 | X | − | 1 | ) |
= | 2 | X | − | 4 | − | 3 | X | + | 1 |
= | - | 1 | X | − | 3 |
- | 1 | X | − | 3 | = | 4 | ( | 1 | − | X | ) |
方程右边 = | 4 | × | 1 | − | 4 | X |
= | 4 | − | 4 | X |
- | 1 | X | − | 3 | = | 4 | − | 4 | X |
- | 1 | X | + | 4 | X | = | 4 | + | 3 |
3 | X | = | 4 | + | 3 |
3 | X | = | 7 |
X | = | 7 | ÷ | 3 |
= | 7 | × | 1 3 |
X | = | 7 3 |
X | = | 2.333333 |